1990
DOI: 10.1099/00221287-136-8-1447
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of oleandomycin by Streptomyces antibioticus: influence of nutritional conditions and development of resistance

Abstract: The influence of different nutritional compounds on oleandomycin biosynthesis by Streptomyces antibioticus was studied, resulting in the design of a chemically defined medium for production of the antibiotic. Of the variety of carbon and nitrogen compounds tested, fructose and aspartic acid (carbon and nitrogen sources, respectively) supported the highest oleandomycin titres. Addition of propionate but not acetate, both precursors of the skeleton of the macrolide lactone ring, stimulated the biosynthesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…Growth responses to various carbon sources were recorded using salts medium 63 (Miller, 1972;Sabater e t al., 1972) containing 1 % (w/v) carbohydrate and 15 mM asparagine (Vilches et al, 1990). Of the carbon sources tested, all three Streptomyces strains were found to utilize fructose and glucose most avidly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth responses to various carbon sources were recorded using salts medium 63 (Miller, 1972;Sabater e t al., 1972) containing 1 % (w/v) carbohydrate and 15 mM asparagine (Vilches et al, 1990). Of the carbon sources tested, all three Streptomyces strains were found to utilize fructose and glucose most avidly.…”
Section: Methodsmentioning
confidence: 99%
“…bacteria, it is important to understand the pathways responsible for sugar catabolism (Martin & Demain, 1980;Hodgson, 1982;Vilches et al, 1990; Delic e t al., 1 992).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the synthesis of antifungal metabolites depends on the amount and type of medium constituents. In fact, it has been shown that the carbon and other nutrient sources strongly affect antibiotic production in different organisms, and glucose in particular, increased antibiotic production potential in the rich medium (Cruz et al, 1999;Vilches et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…So, this medium was used to determine the optimal conditions that enhance antibacterial productivity by Streptomyces tunisiensis SA-13. The key factors that strongly affect microbial metabolites are carbon and nitrogen sources [34]. The results showed that antimicrobial activity was higher in riched medium having sugar and peptone as carbon and nitrogen source respectively.…”
Section: Effect Of Different Culture Mediamentioning
confidence: 99%